Social Studies Learning Needs Analysis Based on Local Wisdom di Rejang Lebong Elementary School - Nasution, Aida Rahmi; Ratnawati, Ratnawati; Supriatin, Atin; Amanisa, Rabbyatul (Al-Mudarris, 2024)
21st-century learning is both a challenge and a great opportunity for teachers in presenting learning innovations that are more contextual and meaningful. Local wisdom is considered to contribute positively to shaping the ability to communicate, collaborate, critically thinking, and also an innovation of students' work because the learning patterns presented are concrete and close to daily activities. Need analysis is one way to obtain data related to teacher and student perspectives on local wisdom-based learning. This research uses a qualitative approach based on case studies with data collection techniques including observation, interviews, and documentation. Data analysis using Creswell includes data display, data reduction, and conclusions. The findings of this study resulted in; 1) based on the needs analysis of the interview this model needs to be developed; 2) the percentage of teachers is 80.85% in the "needed" category and 61.34 students in the "needed" category; 3) Based on observations and interviews, the model is intended to be developed by presenting products in the form of learning modules.